A study of regulatory T cells in allogeneic haematopoietic stem cell transplantation - Danby, RD (2012)
Allogeneic haematopoietic stem cell transplantation (alloHSCT) is an established therapy for many haematological disorders. Unfortunately, the new donor-derived immune system may damage host cells (graft-versus-host disease (GvHD)), causing significant morbidity and mortality. Since regulatory T cells (Tregs) can modulate immune responses, it was hypothesised that Treg numbers in the haematopoietic stem cell grafts and/or peripheral blood may influence the development of GvHD and other transplant-related complications. In this project, a prospective observational clinical study of putative Tregs in human alloHSCT was performed in Oxford. Flow cytometry and methylation-specific qPCR assays were developed to quantify putative Tregs and lymphocyte populations within the grafts and post-transplant blood samples. Although low CD4(+)CD25(+)FOXP3(+)CD127(-/dim) T-cell numbers were not associated with increased incidence of GvHD, low proportions of CD25(+)FOXP3(+)CD127(-/dim) cells in the graft (as a percentage of total CD4(+) T cells) were independently associated with poor engraftment, increased non-relapse mortality and inferior overall survival. Similarly, falling CD4(+)CD25(+)FOXP3(+)CD127(-/dim) T-cell counts over the first three months post-transplant were associated with higher non-relapse mortality and inferior overall survival. In view of these novel findings, strategies that increase CD4(+)CD25(+)FOXP3(+)CD127(-/dim) T cells in alloHSCT may improve clinical outcomes. One possible route for increasing Tregs is through cellular therapy. This project therefore tested the hypothesis that CD4(+)CD25(+)FOXP3(+) Tregs can be produced in vitro from conventional CD4(+) T cells. In the presence of TGFβ and Azacitidine, FOXP3 was expressed in the majority of activated CD4(+) T cells. These cells also had a demethylated FOXP3 TSDR enhancer which is specific to natural Tregs. However, most of these cells produced pro-inflammatory cytokines, for example, TNFα. Therefore, under these conditions, FOXP3 expression was not sufficient to produce a Treg phenotype. It is proposed that current focus for generating Tregs for human clinical trials should be directed towards improving isolation and expansion of ex vivo isolated Tregs.